Analisis Sistem Monitoring Penerimaan Negara dalam Mendukung Akuntabilitas Pengelolaan Keuangan Negara pada Seksi Perbendaharaan di KPPBC TMP C Sumbawa - Wiyanda Anggraini; Sriyatun Sriyatun (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the implementation of the government revenue monitoring system in support of financial management accountability at the Treasury Section of the Sumbawa TMP C Customs and Excise Office. This study employs a qualitative approach using the case study method. Data were collected through in-depth interviews with two informants, the Head of the Treasury Section and a staff member of the Treasury Section and supplemented by secondary data in the form of regulations and relevant documents. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The research results indicate that the state revenue monitoring system has been implemented in an integrated manner through the CEISA application and is capable of supporting real-time monitoring, thereby contributing to improved financial management accountability. The revenue collection and recording processes have been digitized, including the management of excise stamps via the Service User Portal using a self-assessment mechanism. However, several obstacles remain in its implementation, including adjustments to regulatory changes, limitations in network infrastructure, and centralized system management. To maintain data reliability, the Treasury Section continues to conduct internal controls through periodic stock takings and checks and balances. The results of this study indicate that the government revenue monitoring system makes a positive contribution to improving financial management accountability, although it still requires ongoing improvements, particularly in terms of system interface and user-friendliness. This study is expected to provide empirical insights for the development of technology-based government revenue monitoring systems and to enrich research on public sector accountability at the operational level.